2012
DOI: 10.1002/jip.1364
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Similarity Coefficients and the Value of Behavioural Themes in Attempts to Link Serial Arson Offences

Abstract: When relying on crime scene behaviours to link serial crimes, linking accuracy may be influenced by the measure used to assess across‐crime similarity and the types of behaviours included in the analysis. To examine these issues, the present study compared the level of linking accuracy achieved by using the simple matching index (S) to that of the commonly used Jaccard's coefficient (J) across themes of arson behaviour. The data consisted of 42 crime scene behaviours, separated into three behavioural themes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The inclusion of unsolved and apparent one-off crimes was important because, when practitioners are searching for linked crimes in practice, the databases they search contain a mixture of solved, unsolved, serial, and one-off offenses. By including such offenses in our research, this helped to ensure that the findings were more ecologically valid than those produced in the majority of previous research (which failed to include unsolved and one-off offenses; e.g., Bennell & Jones, 2005;Burrell et al, 2012;Ellingwood et al, 2013;Santtila et al, 2005Santtila et al, , 2008Tonkin et al, 2008;Woodhams & Toye, 2007).…”
Section: Datamentioning
confidence: 95%
See 2 more Smart Citations
“…The inclusion of unsolved and apparent one-off crimes was important because, when practitioners are searching for linked crimes in practice, the databases they search contain a mixture of solved, unsolved, serial, and one-off offenses. By including such offenses in our research, this helped to ensure that the findings were more ecologically valid than those produced in the majority of previous research (which failed to include unsolved and one-off offenses; e.g., Bennell & Jones, 2005;Burrell et al, 2012;Ellingwood et al, 2013;Santtila et al, 2005Santtila et al, , 2008Tonkin et al, 2008;Woodhams & Toye, 2007).…”
Section: Datamentioning
confidence: 95%
“…Over the last decade, a growing body of research has sought to develop statistical methods that might underpin computerized crime linkage support tools (e.g., Bennell & Jones, 2005;Burrell et al, 2012;Ellingwood, Mugford, Bennell, Melnyk, & Fritzon, 2013;Santtila, Junkkila, & Sandnabba, 2005;Santtila et al, 2008;Tonkin, Grant, & Bond, 2008;Winter et al, 2013;Woodhams & Labuschagne, 2012;Woodhams & Toye, 2007;Yokota, Fujita, Watanabe, Yoshimoto, & Wachi, 2007). These studies have found support for the two theoretical assumptions that underpin crime linkage (behavioral consistency and distinctiveness 5 ) and have demonstrated moderate to high levels of accuracy when using offender crime scene behavior to distinguish between linked and unlinked offenses (see Bennell, Mugford, Ellingwood, & Woodhams, 2014, for a review).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical research has reflected the broad application of crime linkage, finding support for the principles of behavioural consistency and distinctiveness in burglary (Bennell & Canter, ; Markson, Woodhams, & Bond, ), personal and commercial robbery (Burrell, Bull, & Bond, ; Woodhams & Toye, ), sexual assault (Harbers, Deslauriers‐Varin, Beauregard, & van der Kemp, ; Santtila, Junkkila, & Sandnabba, ; Woodhams & Labuschagne, ), car theft (Davies, Tonkin, Bull, & Bond, ; Tonkin, Grant, & Bond, ), arson (Santtila, Fritzon, & Tamelander, ), and homicide (Salfati & Bateman, ; Santtila et al, ). Support for these principles has also been found using samples containing several crime types (Tonkin & Woodhams, ), both unsolved and solved offences (Woodhams & Labuschagne, ), one‐off and a series of offences (Tonkin, Santtila, & Bull, ), and using different methodologies and data from different countries (Ellingwood, Mugford, Bennell, Melnyk, & Fritzon, ; Tonkin et al, ). Although these empirical studies have found support for the theories of behavioural consistency and distinctiveness, this is often caveated with the notion that these theories do not hold for all offenders, and within all series, to the same extent (Woodhams & Labuschagne, ).…”
Section: Introductionmentioning
confidence: 87%
“…There are many additional transformation functions that are appropriate for linkage data (e.g., groups of behavioral crime variables can be compared with Jaccard's coefficient (Melnyk et al, 2011) or a matching index (Ellingwood et al, 2012)). The selection of appropriate transformation functions is an important step in the linkage process as different transformations will provide different linkage performance (Bennell et al, 2010;Ellingwood et al, 2012;Melnyk et al, 2011;Salo et al, 2012) and can impact the class of models available for linkage. The next section shows how the resulting evidence variables are used to estimate the Bayes factor.…”
Section: Evidence Variablesmentioning
confidence: 99%